Effect of Omega-3 Fatty Acid Supplementation on Periodontal Inflammation and Pocket Depth Reduction - E M Arshad Ali; Kiran Dodani; Ankur Singh Rajpoot; Pallavi Goswami; Varsha Choubey; Aanchal Gupta (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic inflammation of the tooth’s supporting tissues is known as periodontal disease. It causes pockets to develop, attachments to break, and eventually the loss of teeth. Because of their well-known anti-inflammatory qualities, omega-3 fatty acids have been recommended as an additional therapy for periodontal inflammation. Materials and Methods: A randomized controlled study of 60 individuals suffering from persistent periodontitis was carried out. Two groups of participants were randomly assigned: The test group (n = 30) got conventional periodontal treatment with omega-3 fatty acid supplementation (1000 mg/day), while the control group (n = 30) received normal periodontal therapy alone. Measurements of periodontal parameters were made at baseline, 3 months, and 6 months after therapy, including bleeding on probing (BOP) and pocket depth. Paired t-tests and analysis of variance were used in the statistical analysis to determine the significance of the group differences. Results: Participants in the test group showed a greater reduction in probing pocket depth (PPD) and BOP at both 3 and 6 months. Specifically, the mean PPD decreased from 5.4 ± 0.7 mm to 3.0 ± 0.4 mm, and BOP reduced from 71.2 ± 14.5% to 28.3 ± 9.2% in the test group, with both outcomes showing statistically significant differences compared to the control group (P < 0.01). Conclusion: In individuals with chronic periodontitis, omega-3 fatty acid supplementation dramatically improves the decrease of periodontal pocket depth and inflammation when administered as an adjuvant to regular periodontal treatment.